Assessment of sulfide corrosion cracking and hydrogen permeation behavior of ultrafine grain high strength steel. (15th April 2022) - Chen, Lin; Case, Raymundo; Liu, Lianlian; Xiang, Sisi; Castaneda, Homero
Abstract: In this work, the hydrogen permeation behavior and sulfide corrosion cracking susceptibility of ultrafine grain high strength steel were studied under different concentrations of H2 S and pH. The critical sulfide stress cracking factor (KISSC ) displays an exponential decrease with trapped hydrogen concentration in the steel. High content of retained austenite and dislocations contribute to high trap density of atomic hydrogen within the ultrafine grain high strength steel. Austenite absorbed more hydrogen as potential cracking sites while bainite with large grain size helps to maintain sulfide corrosion cracking resistance. Highlights: Hydrogen permeation current increases with increasing H2 S concentration and decreasing pH. High fraction of austenite makes nanostructured steel absorb more hydrogen. An exponential relationship between KISSC and C0 was obtained. The higher the absorbed hydrogen concentration, the lower KISSC .